Improvement of hypertension control and left-ventricular function after cure of primary hyperparathyroidism - Karwacka, Izabela; Kmieć, Piotr; Kaniuka-Jakubowska, Sonia; Pisowodzka, Izabela; Fijałkowski, Marcin; Sworczak, Krzysztof (Frontiers in Endocrinology, 2023)
Introduction Cardiovascular mortality is significantly higher in patients with primary hyperparathyroidism (PHPT) compared to the general population. The role of the renin-angiotensin-aldosterone system (RAAS) as a mediator of cardiovascular pathology in PHPT is unclear, as is the question whether successful parathyroidectomy (PTX) mitigates hypertension (HT), and left-ventricular (LV) dysfunction. Methods In 45 consecutive, hypercalcemic PHPT patients (91% female, 20 normotensive, mean age 54.6 ± 14.6), laboratory examinations, and 24 h ambulatory blood pressure monitoring (ABPM) were performed before, one and six months after successful PTX, while transthoracic echocardiography (TTE) pre- and six months post-PTX. Results Both in patients with normotension (NT) and HT, lower calcemia and parathyroid hormone (PTH) as well as higher phosphatemia were observed on follow-up, while B-type natriuretic peptide, aldosterone, plasma renin activity, and aldosterone-to-renin ratios were comparable. Six months post-PTX, only in patients with HT, median 24-hour SBP/DBP decreased by 12/6 mmHg, daytime SBP by 10, and nighttime DBP by 5 mmHg. Improvement in BP was observed in approximately 78% of patients with HT. Six months post-PTX, TTE revealed: 1) decrease in median LV mass index (by 2 g/m2) and end-diastolic dimension (by 3 mm) among patients with HT; 2) normalization of global longitudinal strain in 22% of patients (comparable between those with NT and HT); 3) a mean 12.7% reduction in left-atrium volume index among patients with HT, which underlay normalization of indeterminate diastolic function in 3 out of 6 patients with HT, who exhibited it at baseline (dysfunction persisted in 2). Conclusions PTX was shown to significantly reduce BP, LV hypertrophy and diastolic dysfunction parameters in PHPT patients with HT, and improve systolic function in all PHPT patients.